Histrionical Blurriness. A God Image Without Features - Agnieszka Małgorzata Krzysztof - Świderska (Jesuit University Ignatianum in Krakow, 2022)
RESEARCH OBJECTIVE: Exploring the specificity of God Image in histrionic personality organization. THE RESEARCH PROBLEM AND METHODS: The main research question is: God Image in histrionic subtype of Personality Organization is similar or different from the God Image in Borderline Personality Organization? Methodological strategy of Qualitative Secondary Analysis with the use of CAQDAS of material gathered in a project concerning God Image in Borderline personality organization (Krzysztof-Świderska, 2017) was performed. THE PROCESS OF ARGUMENTATION: The influence of the preoedipal roots of histrionic personality organization on the development of the specific God Image was argued. RESEARCH RESULTS: Outcomes shed light on certain characteristics of the histrionic God image: idealization and blurriness. The main conclusion is that characteristics of God Image in histrionical patients correspond with Bollas's theoretical approach. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: From a methodological point of view in future research, it is recommended to standardize groups in terms of the phase of therapy. It is also indicated that acting out experienced problems in a religious space could be potentially dangerous to those patients.